2016
DOI: 10.1371/journal.pone.0154773
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous Oxide Emission and Denitrifier Abundance in Two Agricultural Soils Amended with Crop Residues and Urea in the North China Plain

Abstract: The application of crop residues combined with Nitrogen (N) fertilizer has been broadly adopted in China. Crop residue amendments can provide readily available C and N, as well as other nutrients to agricultural soils, but also intensify the N fixation, further affecting N2O emissions. N2O pulses are obviously driven by rainfall, irrigation and fertilization. Fertilization before rainfall or followed by flooding irrigation is a general management practice for a wheat-maize rotation in the North China Plain. Ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 48 publications
(64 reference statements)
1
16
0
Order By: Relevance
“…The stress values for both NMDS plots were lower than 0.12 indicating that these data were well-represented by the two-dimensional ordinations. [Colour figure can be viewed at wileyonlinelibrary.com] genetic potential for N 2 O production and consumption (Morales et al, 2010;Zhong et al, 2014;Gao et al, 2016). In our study, along with the changes in N 2 O production, the transcriptional level of AOB amoA gene was significantly decreased by DMPP in all alkaline soils, while no significant influence of DMPP on AOA transcripts was found in any of the studied soils (Fig.…”
Section: Nitrifier-induced Denitrification Can Be Inhibited By the Nisupporting
confidence: 52%
See 1 more Smart Citation
“…The stress values for both NMDS plots were lower than 0.12 indicating that these data were well-represented by the two-dimensional ordinations. [Colour figure can be viewed at wileyonlinelibrary.com] genetic potential for N 2 O production and consumption (Morales et al, 2010;Zhong et al, 2014;Gao et al, 2016). In our study, along with the changes in N 2 O production, the transcriptional level of AOB amoA gene was significantly decreased by DMPP in all alkaline soils, while no significant influence of DMPP on AOA transcripts was found in any of the studied soils (Fig.…”
Section: Nitrifier-induced Denitrification Can Be Inhibited By the Nisupporting
confidence: 52%
“…The transcriptional analysis of the functional genes is a useful approach to identify the active microbes (Philippot and Hallin, ). The functional genes encoding the enzymes catalysing ammonia oxidation (AOA/AOB amoA genes) and denitrification (the narG , nirS/nirK , nosZ genes) are often used as the proxy for predicting the genetic potential for N 2 O production and consumption (Morales et al ., ; Zhong et al ., ; Gao et al ., ). In our study, along with the changes in N 2 O production, the transcriptional level of AOB amoA gene was significantly decreased by DMPP in all alkaline soils, while no significant influence of DMPP on AOA transcripts was found in any of the studied soils (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…One reason for this is the higher transpiration loss resulting from relatively bigger trees in the precip-change plots (tree height: 10.2 ± 5.0 m, DBH: 10.7 ± 6.3 cm) than that in the control plots (tree height: 7.7 ± 3.5 m, DBH: 9.5 ± 5.2 cm). There were no significant differences in these stand characteristics, but the bigger trees in precip-change plots might have had greater transpiration rates and therefore caused more soil water loss in the summer wet season (Gao et al, 2017). Another reason might be the large amount of precipitation added (55 mm per event).…”
Section: Drivers Of N Transformation Processesmentioning
confidence: 89%
“…Conversely, it has been suggested that the higher C : N ratio of their residues as compared to those of legumes may provide energy (C) for denitrifiers, thereby leading to higher N 2 O losses in the presence of mineral N-NO − 3 from fertilizers (Sarkodie-Addo et al, 2003). In this sense, the presence of cereal residues can increase the abundance of denitrifying microorganisms (Gao et al, 2016), thus enhancing denitrification losses when soil conditions are favorable (e.g., high NO − 3 availability and soil moisture after rainfall or irrigation events, particularly in fine-textured soils) (Stehfest and Bouwman 2006;Baral et al, 2016). Furthermore, winter CCs can also abate indirect gaseous N losses through the reduction of leaching and subsequent emissions from water resources (Feyereisen et al, 2006).…”
Section: Introductionmentioning
confidence: 99%